2020
DOI: 10.1111/jocn.15166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education and counselling on reducing pain and anxiety in women undergoing hysterosalpingography: A randomised controlled trial

Abstract: Aims and objectives:To investigate the effects of education and counselling on anxiety and pain in women undergoing hysterosalpingography (HSG) as part of infertility treatment.Background: The hysterosalpingography has an important diagnostic role in finding the cause of infertility and making a decision on management of treatment. In addition, it is considered a feared procedure in the infertility process and the one about which very little is known. Women often experience anxiety and pain during the HSG proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…A possible explanation is that although undergoing a tubal patency test can be stressful, it does not have a clinically relevant impact on fertility related QoL 6 weeks after the procedure. Also, the fact that women have been given extensive information about the two procedures before enrolling in our RCT, could possibly have led to the procedure having less effect on their quality of life (Handelzalts et al 2016;Guvenc et al 2020). Similar to other studies we found an association between older age and a higher fertility related quality of life (Cusatis et al 2019;Santoro et al 2016)…”
Section: Comparison To Other Literaturesupporting
confidence: 85%
“…A possible explanation is that although undergoing a tubal patency test can be stressful, it does not have a clinically relevant impact on fertility related QoL 6 weeks after the procedure. Also, the fact that women have been given extensive information about the two procedures before enrolling in our RCT, could possibly have led to the procedure having less effect on their quality of life (Handelzalts et al 2016;Guvenc et al 2020). Similar to other studies we found an association between older age and a higher fertility related quality of life (Cusatis et al 2019;Santoro et al 2016)…”
Section: Comparison To Other Literaturesupporting
confidence: 85%
“…Guvenc et al in a randomised control trial also found that patient education and counselling is an effective intervention to reduce the pain score. 23 We used PGE-1 tablets vaginally, the night before in all patients for cervical softening. It facilitates the process and improves tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that in this study, the lowest score on the medical management of illness dimension of self-management was 1, indicating that some patients had a significant lack of knowledge related to anxiety symptom recognition, medication management and emotional management. This reminds healthcare professionals that they should increase education on disease related knowledge for anxious patients, such as through some online live video courses, graphic knowledge push or offline health talks and discharge education, so as to improve patients' disease knowledge and promote self-management [28][29][30].…”
Section: Current Status Of Self-management In Patients With Anxiety D...mentioning
confidence: 99%